PENGARUH PENDIDIKAN KESEHATAN AUDIOVISUAL KANKER PAYUDARA MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP TINGKAT PENGETAHUAN WANITA USIA SUBUR - Eka Tiara Sakina; Sri Utami; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Breast cancer is a serious threat or a malignant disease that is very feared by women, because breast cancer is taking the second place after cervical cancer. This aim of this study is to determine the effect of audiovisual health education on breast cancer through social media Instagram on the women’s knowlegde in childbearing age. This study used a Pre-experimental design, one group pre-test post-test method. This research was conducted in RW 04 and RW 07 in district Rejosari with 34 respondents as the samples and with purposive sampling technique based on inclusion criteria. The measuring instrument used was a questionnaire that has been tested for validity and reliability. The analysis used was univariate analysis and bivariate analysis with the Dependent t test and the Wilcoxon test. The test results of the dependent sample t test results obtained p value 0.157 which means p value> α (0.05). This means that Hο failed to be rejected, it can be concluded that there is no effect of breast cancer health education on the knowledge of women of childbearing age. This is because the respondent's education is high so it is easy for respondents to get information through Instagram, so researchers suggest that in conducting health education using skills. Keywords: Breast Cancer, Health Education, Instagram, Knowledge.